2003
DOI: 10.1348/01446650360703357
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation as a mediator of the relationship between recalled parenting and the clinical correlates of auditory hallucinations

Abstract: The clinical and research implications of the study are outlined, emphasizing dissociation as a potential treatment target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
(36 reference statements)
1
19
0
Order By: Relevance
“…The between-group studies all reported significant effects between dissociative experiences and voice-hearing. The remaining five correlational studies similarly showed significant bivariate associations for the dissociationvoices relationship (Kilcommons & Morrison, 2005;Lysaker & LaRocco, 2008;Offen et al, 2003a;Perona-Garcelán et al, 2012a;Varese et al, 2012), with two studies also employing multiple regression analysis showed that dissociation variables predicted voices when accounting for the effect of other possible predictors (Perona-Garcelán et al, 2008;2012b& Kilcommons & Morrison, 2005. In addition to the above investigations, one study used an experience sampling design to examine the relationship between voices and dissociation in a voice-hearing sample only (Varese et al, 2011b), and found that instances of voices in the daily life of voice-hearers are associated with increased dissociation even after controlling for the effect of comorbid symptoms (paranoia).…”
Section: Psychosismentioning
confidence: 87%
See 3 more Smart Citations
“…The between-group studies all reported significant effects between dissociative experiences and voice-hearing. The remaining five correlational studies similarly showed significant bivariate associations for the dissociationvoices relationship (Kilcommons & Morrison, 2005;Lysaker & LaRocco, 2008;Offen et al, 2003a;Perona-Garcelán et al, 2012a;Varese et al, 2012), with two studies also employing multiple regression analysis showed that dissociation variables predicted voices when accounting for the effect of other possible predictors (Perona-Garcelán et al, 2008;2012b& Kilcommons & Morrison, 2005. In addition to the above investigations, one study used an experience sampling design to examine the relationship between voices and dissociation in a voice-hearing sample only (Varese et al, 2011b), and found that instances of voices in the daily life of voice-hearers are associated with increased dissociation even after controlling for the effect of comorbid symptoms (paranoia).…”
Section: Psychosismentioning
confidence: 87%
“…Twelve studies investigated the relationship between voice-hearing and dissociation in a psychosis sample (Kilcommons & Morrison, 2005;Lysaker & LaRocco, 2008;Maggini, et al, 2002;Offen et al, 2003a;Offen et al, 2003b;Perona-Garcelán et al, 2008;PeronaGarcelán et al, 2010;Perona-Garcelán et al, 2012a;Perona-Garcelán et al, 2012b;Spitzer, 1997;Varese et al, 2011;Varese et al, 2012). Seven studies employed a between-group design.…”
Section: Psychosismentioning
confidence: 99%
See 2 more Smart Citations
“…Experiencing auditory hallucinations as malevolent has been found to be related to paternal overprotection (i.e. being ‘controlling and intrusive’) and low levels of paternal care (124).…”
mentioning
confidence: 99%